2014
DOI: 10.1186/2040-2392-5-18
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the common genetic architecture of social-communication spectrum phenotypes during childhood and adolescence

Abstract: BackgroundSocial-communication abilities are heritable traits, and their impairments overlap with the autism continuum. To characterise the genetic architecture of social-communication difficulties developmentally and identify genetic links with the autistic dimension, we conducted a genome-wide screen of social-communication problems at multiple time-points during childhood and adolescence.MethodsSocial-communication difficulties were ascertained at ages 8, 11, 14 and 17 years in a UK population-based birth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
73
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 52 publications
(81 reference statements)
15
73
0
Order By: Relevance
“…ASD-like behaviours have also been exhibited in SH3 and multiple ankyrin repeat domains 3 (SHANK3) mouse models (Peca et al, 2011) with mutations and copy number variations in SHANK3 being strongly associated with ASD (Durand et al, 2007;Sykes et al, 2009) and with SHANK3 interacting directly with mGluR5 through binding of Homer and phospholipase C (PLC) to regulate signalling (Hwang et al, 2005;Tu et al, 1999). In addition, a recent meta-analysis has demonstrated that mutations in SHANK3 are present in 0.69% of patients with ASD, with SHANK1 and 2 mutations to a lesser extent present in 0.04% and 0.17% respectively (Leblond et al, 2014) with SNPs and CNVs in PLCB1 also recently been identified and linked to ASD (Girirajan et al, 2013;St Pourcain et al, 2014). Furthermore, dysregulation in the methylation status of SHANK3 in post-mortem brains of individuals with ASD versus controls has also been demonstrated as well as inhibition of SHANK3 being shown to cause a reduction in synaptic expression of mGluR5 in hippocampal and cortical neuronal cultures, leading to reduced spine density and mini EPSCs (Verpelli et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…ASD-like behaviours have also been exhibited in SH3 and multiple ankyrin repeat domains 3 (SHANK3) mouse models (Peca et al, 2011) with mutations and copy number variations in SHANK3 being strongly associated with ASD (Durand et al, 2007;Sykes et al, 2009) and with SHANK3 interacting directly with mGluR5 through binding of Homer and phospholipase C (PLC) to regulate signalling (Hwang et al, 2005;Tu et al, 1999). In addition, a recent meta-analysis has demonstrated that mutations in SHANK3 are present in 0.69% of patients with ASD, with SHANK1 and 2 mutations to a lesser extent present in 0.04% and 0.17% respectively (Leblond et al, 2014) with SNPs and CNVs in PLCB1 also recently been identified and linked to ASD (Girirajan et al, 2013;St Pourcain et al, 2014). Furthermore, dysregulation in the methylation status of SHANK3 in post-mortem brains of individuals with ASD versus controls has also been demonstrated as well as inhibition of SHANK3 being shown to cause a reduction in synaptic expression of mGluR5 in hippocampal and cortical neuronal cultures, leading to reduced spine density and mini EPSCs (Verpelli et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…General cognitive ability is highly heritable, but GWAS studies have struggled to find significant effects for common variants, nor has any association been found with low-frequency CNVs (Davies et al 2011;McRae et al 2013;Kirkpatrick et al 2014). GWAS studies for social behavior have faced similar difficulties (Ebstein et al 2010;St Pourcain et al 2013, 2014b). However, a GWAS for educational attainment in over 100,000 individuals identified three SNPs which reached genome-wide significance, and these associations were replicated in a further sample of 25,000 individuals (Rietveld et al 2013), illustrating that very large sample sizes do have the power to detect small contributions from common SNPs to normal phenotypic variation.…”
Section: Intellectual Disability and Autism Spectrum Disordersmentioning
confidence: 99%
“…This data was used in a reconstruction of functional networks linking the antibodies targets to genes relevant to autism (Supplementary table 2). The genes were chosen via GWAS studies by the correlation of relevant SNPs to autistic phenotype (genes) [28][29][30][31].…”
Section: Data Miningmentioning
confidence: 99%